Dopamine D2/3-receptor availability and its association with autonomous motivation to exercise in older adults: An exploratory [11C]-raclopride study - Simonsson, Emma; Stiernman, Lars Jonasson; Lundquist, Anders; Rosendahl, Erik; Hedlund, Mattias; Lindelöf, Nina; Boraxbekk, Carl-Johan (Frontiers in Human Neuroscience, 2022)
Background: Autonomous motivation to exercise occurs when the activity is voluntary and with a perceived inherent satisfaction from the activity itself. It has been suggested that autonomous motivation is related to striatal dopamine D2/3-receptor (D2/3R) availability within the brain. In this study, we hypothesized that D2/3R availability in three striatal regions (nucleus accumbens, caudate nucleus, and putamen) would be positively associated with self-reported autonomous motivation to exercise. We also examined this relationship with additional exploratory analyses across a set of a priori extrastriatal regions of interest (ROI). Methods: Our sample comprised 49 older adults (28 females) between 64 to 78 years of age. The D2/3R availability was quantified from positron emission tomography using the non-displaceable binding potential of [11C]-raclopride ligand. The exercise-related autonomous motivation was assessed with the Swedish version of the Behavioral Regulations in Exercise Questionnaire 2. Results: No significant associations were observed between self-reported autonomous motivation to exercise and D2/3R availability within the striatum (nucleus accumbens, caudate nucleus, and putamen) using semi-partial correlations controlling for ROI volume on D2/3R availability. For exploratory analyses, positive associations were observed for the superior (r = 0.289, p = 0.023) and middle frontal gyrus (r = 0.330, p = 0.011), but not for the inferior frontal gyrus, orbitofrontal cortex, anterior cingulate cortex, or anterior insular cortex. Conclusion: This study could not confirm the suggested link between striatal D2/3R availability and subjective autonomous motivation to exercise among older adults. The exploratory findings, however, propose that frontal brain regions may be involved in the intrinsic regulation of exercise-related behaviors, though this has to be confirmed by future studies using a more suitable ligand and objective measures of physical activity levels.